2015
DOI: 10.4236/jwarp.2015.713084
|View full text |Cite
|
Sign up to set email alerts
|

Yield, Water Use Efficiency and Physiological Characteristic of “Tommy Atkins” Mango under Partial Rootzone Drying Irrigation System

Abstract: This study was conducted to evaluate the yield, water use efficiency and physiologic characteristics of "Tommy Atkins" mango under partial rootzone drying. The experiment was carried out in an orchard of mango in the irrigated perimeter of Ceraíma, BA. Five treatments and six repetitions were used with one tree per experimental plot: 01-Full Irrigation, 100% of ETc, 02-100% of ETc with frequency of alternance (FA) of 15 days, 03-80% ETc with FA of 15 days, 04-60% of ETc with FA of 15 days, 05-40% ETc with FA o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1
13

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 12 publications
4
13
1
13
Order By: Relevance
“…-mar., 2016 180 ( Figure 3) with a reduced water application in the PRD. Santos et al (2015) reported that the stomatal conductance, transpiration and photosynthesis tend to decreased with an increase in the deficit up to 40% of ETc in PRD, confirming the results found in the present work. …”
Section: Physiological Parameterssupporting
confidence: 83%
See 2 more Smart Citations
“…-mar., 2016 180 ( Figure 3) with a reduced water application in the PRD. Santos et al (2015) reported that the stomatal conductance, transpiration and photosynthesis tend to decreased with an increase in the deficit up to 40% of ETc in PRD, confirming the results found in the present work. …”
Section: Physiological Parameterssupporting
confidence: 83%
“…Spreer et al (2009) PRD in a 'Kent' mango orchard in the semi-arid region of the State of Bahia, Brazil, found that the application of 50% of the water volume does not cause significant yield reductions, with PRD alternating every 14 or 21 days. A PRD with 40% of ETc, alternating the irrigation side every 15 days, also maintained the yield and increased water use efficiency in 'Tommy Atkins' mango in a semiarid region, according to Santos et al (2015). The production results of the present work with PRD differs from those found by Spreer et al (2007), Spreer et al (2009), Sant"Ana et al (2009 and Santos et al (2015).…”
Section: Production and Water Use Efficiencycontrasting
confidence: 56%
See 1 more Smart Citation
“…O delineamento foi em blocos casualizados (DBC), com quatro repetições, nove tratamentos, estratégias baseadas na irrigação lateralmente alternada (PRD), conforme Dzikiti, Steppe e Lemeur (2008), Sampaio et al (2010) e Santos et al (2015), sendo para o ano de 2008, primeiro ciclo de avaliação: 1) 25% de redução da lâmina de irrigação (LI) estimada pela evapotranspiração da cultura (ETc) e sete dias de frequência de alternância de lado da planta (FA) na fase de floração (F1), crescimento do fruto (F2) e estabilidade (F3); 2) 25% de LI e 14 dias de FA de F1 e F3; 3) 50% de LI e 7 dias de FA de F1 a F3; 4) 50% de LI e 15 dias de FA de F1 a F3; 5) 25% de LI em F1 e F2, 50% de LI em F3 e 7 dias de FA; 6) 25% de LI em F1 e F2, 50% de LI em F3 e 15 dias de FA; 7) 25% de LI em F1 e 50% de LI em F2 e F3 e 7 dias de FA; 8) 25% de LI em F1 e 50% de LI em F2 e F3 e 15 dias de FA e9) Irrigação plena.…”
Section: Methodsunclassified
“…A maior demanda evapotranspirométrica (ETo) neste mês e as temperaturas mais amenas pela manhã (FARIA, 2014) Ao comparar os valores das características supracitadas nos horários das 10:00 e 13:00, verificou-se que, Ci foi 9,56% menor, gs 66,52% menor, A 56,54% menor, enquanto a temperatura foliar às 13:00 foi 30% maior que no horário das 10:00 e a transpiração não variou entre horários (Tabela 2). A elevação da temperatura causou redução na fotossíntese, corroborando Medina et al (2005) e Machado et al (2010), mas não causou redução na transpiração como observado por Santos et al (2015), o que evidencia mais um efeito enzimático que estomático . Sob concentração de CO2 ambiental, aumento na temperatura modifica as constantes cinéticas da rubisco e aumenta a taxa de oxigenação, preferencialmente à carboxilação, aumenta a fotorrespiração e decresce fotossíntese líquida.…”
Section: Segundo Ciclo De Avaliaçãounclassified